Do previously held vaccine attitudes dictate the extent and influence of vaccine information-seeking behavior during pregnancy? - Richard M. Clarke; Miroslav Sirota; Pauline Paterson (Taylor & Francis Group, 2019)
Pregnancy represents a high information need state, where uncertainty around medical intervention is common. As such, the pertussis vaccination given during pregnancy presents a unique opportunity to study the interaction between vaccine attitudes and vaccine information-seeking behavior. We surveyed a sample of pregnant women (N = 182) during early pregnancy and again during late pregnancy. The variables of vaccine confidence and risk perception of vaccination during pregnancy were measured across two questionnaires. Additional variables of decision conflict and intention to vaccinate were recorded during early pregnancy, while vaccine information-seeking behavior and vaccine uptake were recorded during late pregnancy. 88.8% of participants reported seeking additional information about the pertussis vaccine during pregnancy. Women that had a lower confidence in vaccination (p = .004) and those that saw the risk of pertussis disease as high compared to the risk of side effects from the pertussis vaccination during pregnancy (p = .004) spent significantly more time seeking information about the pertussis vaccination. Women's perception of risk related to vaccination during pregnancy significantly changed throughout the pregnancy (t(182) = 4.685 p< .001), with women perceiving the risk of pertussis disease higher as compared to the risk of side effects from the vaccine as the pregnancy progresses. The strength and influence of information found through seeking was predicted by intention to vaccinate (p = .011). As such, we suggest that intention to vaccinate during early pregnancy plays a role in whether the information found through seeking influences women towards or away from vaccination.